Research of the Meshing Drive Performance of New Arc Tooth Synchronous Belt based on RecurDyn - Guo Jianhua; Wei Lai; Cao Zhongliang; Jiang Hongyuan (Jixie chuandong)
Based on the multi-body dynamics software RecurDyn,a virtual prototyping model of new arc tooth synchronous belt drive is established and simulated. The simulation stress cloud chart shows the synchronous belt bears the maximum load at the pinch-in and out areas of active and driven pulley. Analysis on dynamic virtual prototypes shows that the tooth surfaces are loaded in the pinch-in and pinch-out areas,and belt deflection are the main reasons for the increase of the band load. And the load on the top of the belt tooth can effectively reduce the root load. The polygon effect of the synchronous belt and the internal excitation of the system caused by the meshing impact are the main reasons for the angular velocity fluctuation of the driven wheel. The research of the output speed of the driven wheel shows that the speed fluctuation is a periodic harmonic function.